Four-wave mixing in photonics crystal fibres for wavelength conversion in optical networks - D. J. Barros (2004)
Four-Wave Mixing is one of the few all-optical techniques which provides fully transparent wavelength conversion. Here, we demonstrate Four-Wave Mixing generation in a band of up to 20 nm centred at the zero dispersion wavelength of a photonic crystal fibre (1560 nm). A stable efficiency around -35 dB is maintained across the band using a pump power of 10 dBm. The experimental results are in good agreement with the theoretical results.